Corrosion inhibition of brass in 3% NaCl solution by 3-methyl-1, 2, 4-triazol-5-thione. (April 2015) - Damej, M.; Chebabe, D.; Benmessaoud, M.; Dermaj, A.; Erramli, H.; Hajjaji, N.; Srhiri, A.
Abstract : In this work, a new organic compound as methyl-1, 2, 4-triazole-5-thione (MTS) was tested as brass corrosion inhibitor. It was synthesised and characterised using IR, 1 HNMR and 13 CNMR spectra. The synthesised inhibitor was tested against brass 60Cu–Zn corrosion in 3% NaCl solution using potentiodynamic polarisation and impedance spectroscopy (EIS) as electrochemical methods. In addition, the SEM and EDX were used to characterise the metal surface state. It has been observed that the inhibition efficiency increases with increasing concentration of MTS. The potentiodynamic polarisation results revealed that the inhibitor acts as mixed type one. The EIS spectra indicate that the charge–transfer resistance value increases with increasing MTS concentrations. Scanning electron microscopy results reveal that MTS acts as a good inhibitor. The inhibition efficiency seems to be interpreted by formation of a protective layer on brass surface.